Posted by **shirlee** on Tuesday, May 15, 2012 at 6:38pm.

f(x)=(2x-1)^2(x^2-9)

find f'(x)=0

So first derivative:

f'(x)=16x^3-6x^2-70x+36

0 = 16x^3-6x^2-70x+36

Ok.. I know I should factor it somewhere.. I just couldn't see where..

Thanks!

## Answer this Question

## Related Questions

- calc - find the derivative of y = sqrt(9 - 16x) Use the chain rule. First find ...
- Math - find any stationary points of the function g(x) = (2x-3)square root of 5+...
- Algebra - There are two solutions to | 16x - 5 | = 3. The greatest solution is ...
- algebra - Solve the system by addition or substitution. 16x-4y=20 y=4x-4 I ask ...
- Factor - How do I factor these: 2x2 - 16x + 30 4x^2-9 x^2-5x 5x^2-26x+5 25x^2+4 ...
- Pre-Calculus - Help please If f(x)=8x and g(x)=2x+1 find (fog)(x) 16x^2+8x 16x+1...
- Calculus-derivatives - What is the slope of the tangent of each curve at given ...
- college algebra--please help - solve the following inequality 70x-51<70/x I ...
- calculus - i need to find the derivative using chain rule: (x^2 + 2x - 6)^2 (1-x...
- Math - 5(-3x - 2) - (x - 3) = -4(4x + 5) + 13 Answer Multiply factors. -15x - 10...